ANALISIS KEPERCAYAAN KONSUMEN PADA JASA PENGIRIMAN POS KILAT KHUSUS DI PT. POS INDONESIA (PERSERO) - Dematria Pringgabayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
One product differentiation offered by PT. Pos Indonesia is a special express mail delivery service. Special express mail shipping services have very good prospects, but in reality most of the market share of package delivery services is controlled by private service companies, encouraging consumer motivation, perception and attitudes to be able to produce products / services that have high competitiveness in the effort to win market share. The emergence of these competitors influences PT. Indonesian post. The method used in sampling is Probability Sampling is a random sampling technique that provides equal opportunities for each element / member of the population to be selected as a sample member. Then the number of samples in this study was 100 respondents. Data collection techniques used in this study are questionnaires. Analysis of the data used is quantitative data, with the validity test as many as 23 questions all declared valid because the validity coefficient > 0.3. and reliability testing was declared reliable with a reliable coefficient of 0.6